Discourse on State Capture and Legislative Corruption in the Formation of the National Capital City Law - Pradnya Putri, Sagung Mirah; Dalmau, Rubén Martínez (Kertha Patrika, 2026)
This study examines state capture as a form of legislative corruption in the enactment of Law Number 3 of 2022 concerning the National Capital. Both procedural and substantive aspects of the IKN Law are evaluated against established principles of legislative formation, Constitutional Court jurisprudence, and the foundations of popular governance under the rule of law. Employing a socio-legal approach, the research integrates normative juridical analysis with qualitative empirical methods. The methodology includes analysis of legislation, Constitutional Court decisions, legislative documents, and reports from monitoring institutions, as well as document analysis and interviews with academics and civil society activists to gather empirical insights. The findings indicate that the IKN Law was expedited, providing minimal opportunity for meaningful public participation. This process contravened the transparency and participation principles outlined in the Law on the Formation of Legislation and reaffirmed in Constitutional Court Decision Number 91/PUU-XVIII/2020. Furthermore, the law grants the IKN Authority extensive powers without instituting sufficient checks and balances. The evidence demonstrates state capture, in which legislation is used to legitimize particular interests and undermine democratic oversight. These developments present significant threats to the rule of law, government accountability, and the principle of popular sovereignty within Indonesia’s constitutional framework.